(untitled) (Journal of Economic Research & Business Administration, 2018)
This article aims to benefit from Situational Leadership Model (Hersey and Blanchard, 1977) to suggest new perspectives on project management and resource management. Accordingly it first proposes an integrated, systematic model of project context assessment and management, built upon existing analysis tools and approaches on team members, stakeholders and risks as critical situational aspects of project context or environment. This model underlines situation-based action with respect to tasks, relationships and informations for project management and managers. Accordingly, the suggested model could have various implications for practicing, teaching and learning of Project Management, as well as in other areas of management. The original Situational Leadership Model and proposed Situation-Action Model will then be adapted to suggest a framework for Human and Robot Resource Management, considering new developments and applications in artificial intelligence. Paper will be finalized with suggestions for future work on visualizing analytical relationships on the Situational Leadership model and other relevant conceptualizations.